Increased antibacterial activity of ZnO nanoparticles: Influence of size and surface modification - Lallo da Silva, Bruna [UNESP]; Caetano, Bruno Leonardo [UNESP]; Chiari-Andréo, Bruna Galdorfini [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Elsevier, 2019)
In the current study, the size and surface of ZnO nanoparticle (ZnO NP) suspensions and powders were finely controlled to evaluate their influence on the ZnO antibacterial activity against Staphylococcus aureus and Escherichia coli. The ZnO NP were prepared by the sol-gel method with different reaction times for NP size control and followed by the addition of (3-glycidyloxypropyl) trimethoxysilane (GPTMS) as a surface modifier. The ZnO NP were characterized by different techniques and the antibacterial activity was assessed through the minimum inhibitory concentration assay (MIC), minimum bactericidal concentration assay (MBC) and scanning electron microscopy (SEM). The ZnO NP exhibited significant antibacterial activity against Staphylococcus aureus. The NP size highly influenced the antibacterial activity, which increased with decreasing particle size. The small ZnO NP presented bactericidal activity whereas the largest showed bacteriostatic activity. The use of GPTMS, in general, led to increase of MIC and MBC. The formation of holes in the cell wall of Staphylococcus aureus was evidenced by SEM after contact between the bacteria and ZnO NP. The cytotoxicity assay showed that ZnO NP did not cause a loss of cell viability in the human keratinocyte cell line (HaCat) at the maximum concentration assessed. Thus, this study indicated that 5 nm ZnO NP modified by GPTMS has great potential for use as an inorganic antibacterial material.
Keywords: Bactericidal; Bacteriostatic; Nanoparticles; Size; Surface; ZnO